Perforation of diverticulum of jejunum by foreign body (clinical case) - M.M. Posivnych (Danylo Halytsky Lviv National Medical University, 2017)
Aim:  to highlight the clinical course, diagnosis and treatment of perforation of a diverticulum of the jejunum by a foreign body of vegetable origin (a bay leaf).